THE INFLUENCE OF WORKLOAD, WORK STRESS AND WORK LIFE BALANCE ON EMPLOYEE WORK PERFORMANCE - Tri Mulyani Kartini; Sesri Sellina; Andrianto Prasetya Nugroho (SEAN Institute, 2023)
The rapid growth of business in Bekasi Regency requires companies to always excel in competing, especially for their human resources. This study aims to prove the effect of workload, work stress and worklife balance on work performance on employees of manufacturing companies in the MM2100 area with a population of 185 employees.Sample research as many as 86 employees. The independent variables in this study are workload, work stress and work life balance, while the dependent variable is employee performance. Data analysis is used using the Multiple Linear Regression method. The results of this study indicate that workload has a significant positive effect on work performance1), work stress has a significant positive effect on work performance2), work life balance has a significant positive effect on work performance3), workload, work stress and worklife balance have a significant positive effect on work performance4).